Color of Copper/Copper Oxide. Issue 15 (9th March 2021) - Kim, Su Jae; Kim, Seonghoon; Lee, Jegon; Jo, Yongjae; Seo, Yu‐Seong; Lee, Myounghoon; Lee, Yousil; Cho, Chae Ryong; Kim, Jong‐pil; Cheon, Miyeon; Hwang, Jungseek; Kim, Yong In; et al.
Abstract: Stochastic inhomogeneous oxidation is an inherent characteristic of copper (Cu), often hindering color tuning and bandgap engineering of oxides. Coherent control of the interface between metal and metal oxide remains unresolved. Coherent propagation of an oxidation front in single‐crystal Cu thin film is demonstrated to achieve a full‐color spectrum for Cu by precisely controlling its oxide‐layer thickness. Grain‐boundary‐free and atomically flat films prepared by atomic‐sputtering epitaxy allow tailoring of the oxide layer with an abrupt interface via heat treatment with a suppressed temperature gradient. Color tuning of nearly full‐color red/green/blue indices is realized by precise control of the oxide‐layer thickness; the samples cover ≈50.4% of the standard red/green/blue color space. The color of copper/copper oxide is realized by the reconstruction of the quantitative yield color from the oxide "pigment" (complex dielectric functions of Cu2 O) and light‐layer interference (reflectance spectra obtained from the Fresnel equations) to produce structural color. Furthermore, laser‐oxide lithography is demonstrated with micrometer‐scale linewidth and depth through local phase transformation to oxides embedded in the metal, providing spacing necessary for semiconducting transport and optoelectronics functionality. Abstract : Atomically flat perfect single‐crystal Cu films prepared by the atomic‐sputtering epitaxy method realize the coherent propagation of an oxidation front and display full‐color by controlling the oxide‐layer thickness. More than 50% of the standard red/green/blue color space is covered. Laser‐oxide lithography forming a microscale local oxide embedded in metal is introduced.